Letnikov vs. Marchaud: A Survey on Two Prominent Constructions of Fractional Derivatives - Sergei Rogosin; Maryna Dubatovskaya (Mathematics, 2017)
In this survey paper, we analyze two constructions of fractional derivatives proposed by Aleksey Letnikov (1837–1888) and by André Marchaud (1887–1973), respectively. These derivatives play very important roles in Fractional Calculus and its applications.